A little brains, a little talent [compact disc] - Rainbow, Randy, 1981- (Broadway Records, 2021)
On his first full-length studio album, three-time Emmy-nominated comedian, singer, and viral star Randy Rainbow delivers a glittery potpourri of Broadway standards, popular parodies, and other surprises. With two brand new original songs, the album also features guest stars Tituss Burgess, Josh Gad, Sean Hayes, and more. The album is executive produced and arranged by Jesse Kissel.